Impact of Traveling to Visit Friends and Relatives on Chronic Disease Management. Issue 2 (31st January 2013) - Gurgle, Holly E.; Roesel, David J.; Erickson, Tiffany N.; Devine, Emily Beth
Abstract : Background: Travelers visiting friends and relatives (VFR) are known to be at high risk of acquiring infectious diseases during travel. However, little is known about the impact of VFR travel on chronic diseases. Methods: This was a nonrandomized, retrospective observational study. Patients were adult VFR travelers who received care from an internal medical clinic serving immigrants and refugees. The primary objective was to determine the impact of VFR travel on markers of chronic disease management including: blood pressure, glycosylated hemoglobin, body mass index, serum creatinine, and anticoagulation. Results: Of the 110 VFR travelers in our study, N = 48 traveled to Africa and N = 62 traveled to Asia for a mean duration of 59 (range 21–303) days. Of the 433 counseling points discussed at pre‐travel visits, 71% were infectious disease prevention, 16% chronic disease related, and 13% travel safety. A total of 63 patients (57%) reported one or more health problems while traveling. Of these, 35 patients (32%) experienced a problem related to a chronic condition. In comparison, 24 (22%) patients experienced an acute infection. Sixty percent of patients were nonadherent to medications during travel. An average increase in diastolic blood pressure of 3.6 mmHg among patients with hypertension was the only statistically significant change in a chronic disease marker when values before and after travel were compared. Subgroup analysis revealed that travel to Africa and nonadherence to medications were also associated with worsening blood pressure control, and patients traveling to Africa experienced a decrease in body mass index. Conclusions: This study identified a high proportion of problems related to chronic conditions experienced during VFR travel, while pre‐travel appointments tended to focus on infectious disease prevention. A greater emphasis on medication adherence and chronic disease management during VFR travel is also needed during pre‐travel preparations.